Entrepreneurial Literacy and Digital Mindset as Catalysts for Online Business Readiness: A Systematic Literature Review (International Journal of Economics and Management Research, 2026)
Global development in digital technology have driven the transformation of business models towards online ecosystems, requiring individuals and organizations to have adaptive online business readiness. The growing potential of e-commerce, driven by the massive number of internet users, presents a strategic opportunity.However, many students and young entrepreneurs do not yet have an adequate digital mindset to compete.The urgency of this research lies in the need to understand how entrepreneurship education and digital mindset can act as catalysts in preparing business actors to enter the online business world. This study uses the Systematic Literature Review method with stages of identification, selection, and synthesis of scientific articles, as well as bibliometric analysis using VOSviewer. The results show that the combination of entrepreneurship education and strengthening the digital mindset can improve online business readiness to include the ability to utilize artificial intelligence (AI) technology for marketing, the use of data analytics for decision making, and automated online store management. Additionally, there is a digital literacy gap among students and SME entrepreneurs that can be bridged through a digital project-based entrepreneurship curriculum. The implications of this research encourage universities and policymakers to design entrepreneurship programs that emphasize digital transformation, the use of AI.